Diffusion Behaviors of Integrins in Single Cells Altered by Epithelial to Mesenchymal Transition. Issue 5 (18th December 2021) - Yuan, Jing‐Wen; Zhang, Yu‐Ning; Liu, Yu‐Ru; Li, Wei; Dou, Shuo‐Xing; Wei, Yan; Wang, Peng‐Ye; Li, Hui
Abstract: Cell morphology and migration depend critically on the adhesions on the extracellular matrix (ECM), determined by the transmembrane protein integrins. The epithelial to mesenchymal transition (EMT) is a prominent transformation process in which adherent cells acquire a mesenchymal phenotype and a promoted migration. EMT plays important roles in embryonic development and cancer metastasis, and its hallmarks include the acquisition of front‐back cell polarity and loss of cell–cell contact. However, how integrins dynamically regulate cell‐ECM adhesions and cellular behaviors during EMT is still unclear. Using single‐particle tracking of β1‐integrins labeled with quantum dots, the temporal‐spatial on‐membrane dynamics of integrins in the EMT of MCF10A cells is revealed. β1‐integrins exhibit significantly enhanced dynamics, which temporally behave more diffusive and less immobilized, and spatially become distributed asymmetrically with front regions being more dynamic. These dynamic alterations are shown to arise from microtubule remodeling in EMT. The results shed new light on the EMT mechanism from the cell‐ECM adhesion perspective, and suggest that the enhanced integrin diffusion may represent as a new hallmark of EMT. Abstract : Transmembrane protein integrins, as a key component of cell adhesions connecting cells to extracellular matrix, are labeled with single quantum dots through an antibody–biotin–streptavidin strategy. By single‐particle tracking of integrins on living‐cell membranes, a significant enhancement in integrin diffusion dynamics during the epithelial‐mesenchymal transformation (EMT) is discovered. This enables better identification of EMT at the single‐cell level than traditional biological methods.